2018
DOI: 10.7150/ijms.27181
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Oxidative Stress Effects on Senescence Patterning of Human Adult and Perinatal Tissue-Derived Stem Cells in Short and Long-term Cultures

Abstract: Human Mesenchymal Stem Cells (hMSCs) undergo senescence in lifespan. In most clinical trials, hMSCs experience long-term expansion ex vivo to increase cell number prior to transplantation, which unfortunately leads to cell senescence, hampering post-transplant outcomes.Hydrogen peroxide (H2O2) in vitro represents a rapid, time and cost-effective tool, commonly used as oxidative stress tantalizing the stem cell ability to cope with a hostile environment, recapitulating the onset and progression of cellular sene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 73 publications
2
29
0
Order By: Relevance
“…De Witte et al reported that long-term expansion induced aging of hUC-MSCs exhibiting stable phenotype but reduced immunosuppressive properties from P4 to P12 [39]. Facchin et al reported that umbilical cord Wharton's Jelly-derived MSCs showed higher antioxidant ability to senescence than human adipose tissue-derived MSCs at high subculture passages, and they considered that the age of tissue donors is likely to be the main cause of senescence [40]. Moreover, recently, studies found that transcriptome and epigenetic regulations changes of hUC-MSCs occurred during long-term expansion [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…De Witte et al reported that long-term expansion induced aging of hUC-MSCs exhibiting stable phenotype but reduced immunosuppressive properties from P4 to P12 [39]. Facchin et al reported that umbilical cord Wharton's Jelly-derived MSCs showed higher antioxidant ability to senescence than human adipose tissue-derived MSCs at high subculture passages, and they considered that the age of tissue donors is likely to be the main cause of senescence [40]. Moreover, recently, studies found that transcriptome and epigenetic regulations changes of hUC-MSCs occurred during long-term expansion [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies treating animal MSCs with ascorbic acid, or with an antioxidant cytokine C1q and tumor necrosis factor related protein 9 (CTRP9) [144], have also shown promise and need to be tested on human MSCs. In terms of selecting MSC tissue source for expansion, apart from tissue's propensity for certain lineage differentiation or trophic factor secretion, greater consideration should be given to MSC oxidative stress resistance [145] and desirably, longer onset of senescence. Even amongst perinatal cells, known to reach senescence later than adult tissue-MSCs [146], tissue specific differences exist, as shown recently in Kwon et al study [147].…”
Section: Outlook and Future Directionsmentioning
confidence: 99%
“…Previous reports have induced oxidative stress in vitro by treating cells with H 2 O 2 for 24 h [ 25 , 26 ]. However, ADSCs appear to be particularly susceptible to H 2 O 2 -dependent oxidative stress, with 1 or 2 h of exposure being sufficient to impair ADSC activity [ 27 , 28 ]. Thus, in this study, we induced oxidative stress in ADSCs by exposing these cells to different concentrations of H 2 O 2 for 2 h ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a recent study corroborated the impairment of ADSCs by oxidative stress. Several studies have also indicated that, compared to other cells, stem cells are more susceptible to damage due to free radicals [ 27 ]. Thus, the effect of oxidative stress on stem cells should be taken into consideration for the application of stem cell therapy and endogenous regeneration.…”
Section: Discussionmentioning
confidence: 99%